Displacement due to armed conflict and violence in childhood and adulthood and its effects on older adult health: The case of the middle-income country of Colombia - Mary McEniry; Rafael Samper-Ternent; Carlos Cano-Gutierrez (Elsevier, 2019)
Large population displacement in developing economies due to internal armed conflict and violence is of international concern. There has been relatively little research on the long-term consequences of displacement on older adult health among populations characterized by rapid demographic, epidemiological, and nutritional transitions during the 20th century. We examine displacement in the middle-income country of Colombia, which experienced these rapid transitions and a large population displacement over the last 50-60 years due to internal armed conflict and violence. Using a nationally representative survey of adults 60 years and older, SABE-Colombia (2014-2015, n = 23,694), we estimate the degree to which displacement relative to those never displaced is associated with older adult health (self-reported health, major illness/stress, at least one chronic condition, heart disease), controlling for age, gender, SES (socioeconomic status), residence, early life conditions (infectious diseases, poor nutrition, health, SES, family violence), and adult behavior (smoking, exercise, nutrition). We found (1) strong associations between poor early life conditions and older adult health with little attenuation of effects after controlling for displacement, adult SES, and lifestyle; (2) strong associations between displacement and self-reported health; along with poor early life conditions, displacement increases the chances of poor health at older ages; (3) significant positive interaction effects between childhood infections and displacement during young adulthood for older adult stress/major illness, suggesting the importance of the timing of displacement; (4) significant interaction effects between childhood infections and being displaced during childhood, indicating lower levels of older adult stress/major illness and suggesting the possibility of resilience due to childhood adversity. We conclude that displacement compounds the effects of poor early life conditions and that timing of displacement can matter. The results raise the possibility of similar patterns in the health of aging populations in low-income countries that also experience displacement and rapid demographic and epidemiological transitions.